2014
DOI: 10.1186/2047-217x-3-21
|View full text |Cite
|
Sign up to set email alerts
|

A dataset comprising 141 magnetic resonance imaging scans of 98 extant sea urchin species

Abstract: BackgroundApart from its application in human diagnostics, magnetic resonance imaging (MRI) can also be used to study the internal anatomy of zoological specimens. As a non-invasive imaging technique, MRI has several advantages, such as rapid data acquisition, output of true three-dimensional imagery, and provision of digital data right from the onset of a study. Of particular importance for comparative zoological studies is the capacity of MRI to conduct high-throughput analyses of multiple specimens. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Corfield et al, 2008a; Berquist et al, 2012; Zeigler et al, 2014]. Recent studies have demonstrated the utility of MRI for comparative brain morphology in marine mammals [Marino et al, 2001a, b; Montie et al, 2008; Oelschlager et al, 2010; Berns et al, 2015], birds [Corfield et al, 2008a, b], reptiles [Hoops et al, 2014], teleosts [Van der Linden et al, 2004; Ullmann et al, 2010a, b, c] and cartilaginous fishes [Pradel et al, 2009; Yopak et al, 2009, 2010a; Yopak and Frank, 2007], which provides invaluable data on the size and precise anatomical position of major neuroanatomical features and allows for the non-invasive assessment of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Corfield et al, 2008a; Berquist et al, 2012; Zeigler et al, 2014]. Recent studies have demonstrated the utility of MRI for comparative brain morphology in marine mammals [Marino et al, 2001a, b; Montie et al, 2008; Oelschlager et al, 2010; Berns et al, 2015], birds [Corfield et al, 2008a, b], reptiles [Hoops et al, 2014], teleosts [Van der Linden et al, 2004; Ullmann et al, 2010a, b, c] and cartilaginous fishes [Pradel et al, 2009; Yopak et al, 2009, 2010a; Yopak and Frank, 2007], which provides invaluable data on the size and precise anatomical position of major neuroanatomical features and allows for the non-invasive assessment of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…MRI data for one intact museum specimen each of A. cavernosus (27 mm TL) and A. cordatus (29 mm TL) previously obtained using a Pharmascan 70/16 MRI system (Bruker Biospin GmbH, Ettlingen, Germany) were integrated into the present study. Information on specimen preparation for MRI and scanning parameters has been published elsewhere ( Ziegler and Mueller, 2011 ; Ziegler et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…This publication encouraged further submissions and publications from this community, such as 141 magnetic resonance imaging scans of 98 extant sea urchin species [96], three high-resolution microCT scans of brooding brittle stars [40], as well as a coordinated publication with journal, PLOS One [22], publishing the nearly 40GB of microCT data supporting a paper describing, in high resolution and 3D, the morphological features commonly used in earthworm taxonomy [41]. Despite some of the folders being close to 10GB in size, the data reviewers were able to retrieve each of those in as little as half an hour using our high-speed Aspera internet connection.…”
Section: Tools For Taxonomy 20: Sea Urchins Earthwormsmentioning
confidence: 95%